Depoliticizing Public Action by Politicizing Issues, Practices and Actors. The Role of Resilience Thinking in a Program of the Cariplo Foundation - d'Albergo, Ernesto; Moini, Giulio (PARTECIPAZIONE E CONFLITTO, 2017)
We are apparently living in an age of "hyperdepoliticisation". But what is meant today by de-politicization and how does this phenomenon impact upon the forms taken by political functions in con-temporary complex societies? The aim of this article is that of answering these questions through a re-search-based analysis of the specific role played in depoliticization processes by the use of the concept of resilience and resilience thinking, analyzing the "Resilient Communities" (Comunità Resilienti) program of the Cariplo Foundation. We argue that an intertwined and complementary movement between the depo-liticization of public action and politicization of collective action carried out by non-political actors exists, which does not extirpate the political from social processes, but alters its qualities, characteristics and borders. Such dual movement is composed of pro-active and reactive forms of both depoliticization and politicization, which are defined and investigated in the article, putting empirical evidence against the background of theoretical discussion.